The effect of mirtogenol towards the changes in retinal nerve fiber layer thickness and visual field in primary open angle glaucoma - Astriviani Widyakusuma; Widya Artini; Virna Dwi Oktariana; Joedo Prihartono (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Objective: To evaluate the effect of Mirtogenol towards the changes in retinal nerve fiber layer (RNFL) thickness and visual field in patients with primary open angle glaucoma (POAG) with controlled IOP. Methods: This is a prospective, double blind, randomized study. Forty one POAG patients with IOP ≤ 18 mmHg were randomly assigned to receive either Mirtogenol or placebo. Changes in RNFL thickness and mean deviation of visual fields were evaluated before the treatment, as well as 4 weeks and 8 weeks after the treatment. Patients were asked for any side effects during the treatment period. Result: The average RNFL thickness in the Mirtogenol group decreased -0.70±1.63 μm from 87.29±19.39 μm before the treatment to 86.58±19.43 μm after 8 weeks of treatment, however the change was not significant (p=0.121). The average RNFL thickness in the placebo group decreased -1.74±1.79 μm from 97.14±17.19 μm before the treatment to 95.40±18.56 μm after 8 weeks of treatment, the change was statistically significant (p< 0.001). The average MD of visual field in the Mirtogenol group increased 0.542±1.93 dB after 8 weeks of treatment while the MD of visual field in the placebo group decreased -0.083±1.36 dB after 8 weeks of treatment. Hoewever the changes in MD of visual field was not significant (p>0.05). No side effect was found throughout the study. Conclusion: Mirtogenol seemed to maintain retinal nerve fiber layer thickness and increased mean deviation of visual fields.